Modern Ideas About Some Diseases of Livestock Workers (Literature Review ) - K.Ibrokhimov (Scholars Digest Publishing, 2023)
Man interacts with the external environment that surrounds him. Water, air, plants, animal life, food products, habitat, clothing, noise, vibration, radiation, various drugs, biological preventive drugs, modern airliners, various toxic chemicals used against agricultural pests and others are the environment that surrounds a person. The listed factors directly affect a person's physical and mental health. Mutagenic (oncogenic, teratogenic) factors, which are increasing in the biosphere due to environmental pollution, cause an increase in hereditary diseases. Factors affecting human health • 1. Environment - 20% • 2. Heredity - 20% • 3. Lifestyle - 50% • 4. Health care - 10%.
Keywords: Environment, lifestyle, physical and mental health, hereditary diseases, noise, vibration, radiation exposure.